An Exploration of Human D-Crystallin Affinity for Potential Aggregation Inhibitors: A Molecular Docking Investigation - FLOARE, Călin G.; PÎRNĂU, Adrian; MIC, Mihaela; MATEI, Elena (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Cataract, the leading cause of blindness worldwide, is characterized by the presence of a cloudy area in the eye lens resulting in a loss of transparency. A number of mechanisms contribute to the longevity and transparency of the human lens, a reducing and oxygen deficient environment, the presence of UV-filters, and most importantly a unique supramolecular organization of its structural proteins, the α-, β- and γ-crystallins. With advancing age, progressively, or due to some mutations, this fragile equilibrium can be perturbed, causing γ-crystallin insolubilization, misfolding, fragmentation and aggregation. In this study, we performed a comparative molecular docking analysis of several experimentally investigated molecules of natural origin, that might protect γ-crystallins from destabilization and aggregation. Our specific protein targets are wild-type human γD-crystallin, and its mutant P23T γD-crystallin, associated with congenital cataract. Thirteen phytochemicals were investigated as potential inhibitors of γD-crystallin aggregation, and we compared their binding energies with those of lanosterol, an ingredient present in over-the-counter eye products, to prevent cataracts. We performed a detailed comparative molecular docking analysis and we found that the binding energies of lanosterol outcompete those of all the other investigated potential natural inhibitors.